Sphingolipid Transport to the Apical Plasma Membrane Domain in Human Hepatoma Cells Is Controlled by PKC and PKA Activity: A Correlation with Cell Polarity in HepG2 Cells - Zegers, Mirjam M.P. (The Rockefeller University Press, 1997)
The regulation of sphingolipid transport to the bile canalicular apical membrane in the well differentiated HepG2 hepatoma cells was studied. By employing fluorescent lipid analogs, trafficking in a transcytosis-dependent pathway and a transcytosis-independent (‘direct') route between the trans-Golgi network and the apical membrane were examined. The two lipid transport routes were shown to operate independently, and both were regulated by kinase activity. The kinase inhibitor staurosporine inhibited the direct lipid transport route but slightly stimulated the transcytosis-dependent route. The protein kinase C (PKC) activator phorbol-12 myristate-13 acetate (PMA) inhibited apical lipid transport via both transport routes, while a specific inhibitor of this kinase stimulated apical lipid transport. Activation of protein kinase A (PKA) had opposing effects, in that a stimulation of apical lipid transport via both transport routes was seen. Interestingly, the regulatory effects of either kinase activity in sphingolipid transport correlated with changes in cell polarity. Stimulation of PKC activity resulted in a disappearance of the bile canalicular structures, as evidenced by the redistribution of several apical markers upon PMA treatment, which was accompanied by an inhibition of apical sphingolipid transport. By contrast, activation of PKA resulted in an increase in the number and size of bile canaliculi and a concomitant enhancement of apical sphingolipid transport. Taken together, our data indicate that apical membrane-directed sphingolipid transport in HepG2 cells is regulated by kinases, which could play a role in the biogenesis of the apical plasma membrane domain.